Pengaruh Moralitas Pajak, Good Governance dan Budaya Pajak terhadap Kepatuhan Wajib Pajak - Baharudin Saga; Yunus Nurhasan; Rananda Septanta; Khuzaeni Khuzaeni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Taxpayer compliance is a critical factor in ensuring the effectiveness of tax revenue collection and supporting national development. However, in practice, many taxpayers fail to fulfill their obligations voluntarily due to limited awareness, distrust in government institutions, and insufficient internalization of tax-related norms. This study aims to examine the influence of Tax Morality, Good Governance, and Tax Culture on taxpayer compliance. The research employed a quantitative approach with a survey method, conducted at the Primary Tax Office of Pondok Aren, South Tangerang. The study population consisted of individual taxpayers, with a sample of 100 respondents selected through a simple random sampling technique. Data were collected using structured questionnaires with closed-ended Likert-scale questions and analyzed using multiple linear regression with SPSS version 27. The results indicate that tax morality does not significantly affect taxpayer compliance, suggesting that individual ethical awareness alone is insufficient without external support. In contrast, good governance and tax culture have a significant positive effect, highlighting the importance of transparency, accountability, and social norms in fostering voluntary compliance. Simultaneously, the three variables collectively show a significant impact on taxpayer compliance, emphasizing the necessity of integrating individual ethics, effective governance, and a strong tax culture to achieve higher compliance levels. These findings imply that fiscal policies should prioritize improving governance practices and promoting tax culture education to enhance taxpayer adherence.